2002
DOI: 10.1103/physrevb.66.020403
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic magnetoresistance over 3000% in Ni nanocontacts at room temperature

Abstract: This paper reports ballistic magnetoresistance ͑BMR͒ measurements in Ni nanocontacts made by electrodeposition. BMR in excess of 3000% is observed at room temperature and the observed large values of BMR are obtained in switching fields of only a few hundred oersteds. The results are attributed to spindependent electron transport across nanometer sharp domain walls within the nanocontacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
4
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 13 publications
6
113
4
5
Order By: Relevance
“…This means that, in addition to the size of the nanocontact, its magnetoresistance is also affected by other factors. The Ni ferromagnetic nanocontacts fabricated by mechanical and electrodeposition methods with magnetoresistance values > 70% at room temperature have been reported [6,7,22]. The applied magnetic field alters the interaction between the two anisotropic interfaces, and the contribution of this change to the BMR of the ferromagnetic nanocontacts can not be ruled out yet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that, in addition to the size of the nanocontact, its magnetoresistance is also affected by other factors. The Ni ferromagnetic nanocontacts fabricated by mechanical and electrodeposition methods with magnetoresistance values > 70% at room temperature have been reported [6,7,22]. The applied magnetic field alters the interaction between the two anisotropic interfaces, and the contribution of this change to the BMR of the ferromagnetic nanocontacts can not be ruled out yet.…”
Section: Resultsmentioning
confidence: 99%
“…The BMR effects of ferromagnetic nanocontacts from 70% to 3000% [7], and even up to infinity [9], at room temperature have been reported in recent years. However, some experiments have shown that high BMR at room temperature is because of structural changes in the applied magnetic field and not because of a giant spin valve effect [10,11].…”
mentioning
confidence: 99%
“…The preferred conductance values are indicated by a broad maximum around 1.3G 0 and a second one around 2.5G 0 . Usually, a splitting of these maxima would have been expected because of the so--called ballistic magnetoresistance (BMR) [64,65], where the number of fully transmitted conductance channels changes upon applying a magnetic field. In particular, lifting the spin degeneracy modifies the number of modes for spin-up and spin-down subbands, which manifests itself in a magnetic field dependent opening and closing of discrete conductance channels of the contact leading to discrete conductance steps in the order of e 2 /h [66,67].…”
Section: Ferromagnetic (Co) Single-atom Contactsmentioning
confidence: 99%
“…Bimetallic atomic wires are the most promising objects for construction of new nanoelectronics and spintronics devices [1,2]. Bimetallic atomic nanowires possess the unique magnetic [3,4,8,11] and conductive [2,5] properties, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic atomic nanowires possess the unique magnetic [3,4,8,11] and conductive [2,5] properties, i.e. spin polarized tunnel current, spinfiltering properties [5], giant magnetoresistance [2,12] and giant magnetic anisotropy [11].…”
Section: Introductionmentioning
confidence: 99%